设int a=12,则执行完语句“a+=a-=a*a;”后,a的值是()。
A: 522
B: 264
C: 144
D: -264
A: 522
B: 264
C: 144
D: -264
D
举一反三
- 设int a=12,则执行完语句a+=a-=a*a后,a的值是 A: 552 B: 264 C: 144 D: -264
- 设int a=12,则执行完语句a+=a-=a*a后,a的值是 ( ) A: 552 B: 264 C: 144 D: -264
- 设 int a=12,则执行完语句a+=a-=a*a后,a的值是( ) A: 552 B: 264 C: 144 D: -264
- 设 int a=12,则执行完语句a+=a-=a*a后,a的值是___( )___ A: 552 B: 264 C: 144 D: -264
- 设int a=12,则执行完语句a+=a-=a*a后,a的值是________ A: 552 B: 264 C: 144 D: -264
内容
- 0
设int a=12,则执行完语句a+=a-=a*a后a的值是() A: 552 B: 264 C: 144 D: -264
- 1
设 int a=12,则执行完语句a+=a-=a*a后,a的值是____D____ A: 552 B: 264 C: 144 D: -264
- 2
int a=12,则运行完语句a+=a-=a*a后,a的值是( ) A: -264 B: 552 C: 264 D: 144
- 3
03410071:已知int a=12,执行完语句a+=a-=a*a后,a的值是( )。 A: 552 B: 144 C: 264 D: -264
- 4
若有定义语句:int a=12;,则执行语句:a+= a-= a*a;后,a的值是( )。 A: -264 B: 144 C: 552 D: 264